Enhanced anti-ageing and wound healing properties of Ficus religiosa L. bark, leaf and aerial root extract in human keratinocytes cell line (HaCaT) - Pandey, Prem; Seo, Hyo Hyun; Kim, Hye-In; Ryu, Seung Hwan; Dingre, Medini; Moh, Sang Hyun; Kulkarni, Atul; Parasharami, Varsha A. (Vegetos, 2020)
<span style="color: rgb(51, 51, 51); font-family: Georgia, Palatino, serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(252, 252, 252);">Plants have played a vital role in curative and preventive healthcare. <i style="box-sizing: inherit; color: rgb(51, 51, 51); font-family: Georgia, Palatino, serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(252, 252, 252);">Ficus religiosa<span style="color: rgb(51, 51, 51); font-family: Georgia, Palatino, serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(252, 252, 252);"> L., a medicinally important tree has been used as a traditional medicine to treat various ailments and skin diseases. However, its skin anti-ageing properties are not yet scientifically evaluated. Here we report the comparison of <i style="box-sizing: inherit; color: rgb(51, 51, 51); font-family: Georgia, Palatino, serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(252, 252, 252);">F. religiosa<span style="color: rgb(51, 51, 51); font-family: Georgia, Palatino, serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(252, 252, 252);"> bark (FRAqB), leaf (FRAqL) and aerial-roots (FRAqAR) extracts for skin anti-ageing and wound healing properties. FRAqB, FRAqL and FRAqAR extracts preparation, cell culture, RNA isolation, real time PCR, astringent activity and wound healing assay were carried out using standard methods. Axio Observer FL-microscope and ImageJ software were used for wound healing assay analysis. The real time PCR study reveals that matrix metalloproteinase-1 (MMP) RNA was downregulated to 75% and 95% for FRAqB and FRAqAR, respectively. For procollagen C-endopeptidase enhancer 1 (PCOLCE), FRAqB and FRAqL enhanced RNA levels by 500% and 300%, respectively. FRAqB and FRAqL increased wound healing area to about 60% and FRAqAR by 50%. All three extracts demonstrated astringent activity which is significant for skin tightening. The study proves that extracts of <i style="box-sizing: inherit; color: rgb(51, 51, 51); font-family: Georgia, Palatino, serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(252, 252, 252);">F. religiosa<span style="color: rgb(51, 51, 51); font-family: Georgia, Palatino, serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(252, 252, 252);"> are prominent candidates for pharmaceutical and cosmetic applications such as skin anti-ageing and wound healing.